Option Exercise Games: An Application to the Equilibrium Investment Strategies of Firms - Grenadier, Steven R. (Review of Financial Studies, 2002)
Under the standard real options approach to investment under uncertainty, agents formulate optimal exercise strategies in isolation and ignore competitive interactions. However, in many real-world asset markets, exercise strategies cannot be determined separately, but must be formed as part of a strategic equilibrium. This article provides a tractable approach for deriving equilibrium investment strategies in a continuous-time Cournot–Nash framework. The impact of competition on exercise strategies is dramatic. For example, while standard real options models emphasize that a valuable “option to wait ” leads firms to invest only at large positive net present values, the impact of competition drastically erodes the value of the option to wait and leads to investment at very near the zero net present value threshold. The real options approach to analyzing investment under uncertainty has become part of the mainstream literature of financial economics. The real options approach to investment now typically comprises an entire chapter in corporate finance textbooks [see, e.g., Brealey and Myers (2000) and Van Horne (1998)]. Essentially the real options approach posits that the oppor-tunity to invest in a project is analogous to an American call option on the investment opportunity. Once that analogy is made, the vast and rigorous machinery of financial options theory is at the disposal of real investment analysis. The real options approach is well summarized in Dixit and Pindyck (1994) and Trigeorgis (1996).1 A feature that the vast majority of real options articles have in common is the lack of strategic interaction across option holders. Investment (exercise) strategies are formulated in isolation, without regard to the potential impact of other firms ’ exercise strategies. The standard starting point for such models is an exogenous process for underlying asset values (e.g., the stock price in